Executive functions in sarcoidosis: a neurocognitive assessment study - Bilgin Topçuoğlu, Özgür; Kavas, M; Alibaş, Hande; Afşar, Gülgün Çetintaş; Arınç, Sibel; Midi, İpek and Elmacı, Neşe Tuncer (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Sarcoidosis is a multisystem, inflammatory disease characterized by non-caseating granulomas in multiple organs. Neuropsychological impairment has been told to be present in about 10% of sarcoidosis patients with diagnosed central nervous system (CNS) involvement. Both anatomical lesions and changes in immunological parameters in sarcoidosis may cause cognitive impairment. Based on the information that soluble interleukin-2 receptors (sIL-2R) and tumour necrosis factor alpha (TNF-α) which plays a role in the pathogenesis of sarcoidosis accumulate in the basal ganglia and prefrontal structures, impairment in executive functioning is most likely to be expected in sarcoidosis. In this study we aimed to evaluate executive functions in sarcoidosis patients. Method: This study included 21 sarcoidosis patients (14 females, 7 males) and 21 healthy controls (12 females, 9 males). All participants were given Beck Depression Inventory- Second Edition, Stroop Test, Verbal Fluency Tests, Digitspan Forward Test, Digitspan Backwards Test and Trail Making Test Part- B. Test results of sarcoidosis patients were compared with healthy controls. Results: No significant difference was detected between sarcoidosis patients and healthy controls by means of neuropsychological assessment tests (p>0.05). Conclusion: Our study showed that sarcoidosis patients did not have impairment in executive functions. This result may be commented in two different outcomes. One of them, would be the probable necessity of additional electrophysiological or radiological tests including detailed paradigmas for evaluation of executive functions. Secondly the effect of therapeutics used in sarcoidosis (steroids and/or immunosuppressants) on cognition should be questioned regarding the controversial previous data which released cognitive decline in sarcoidosis.